Quantitative data analysis in communication research: first edition / Ahlam Abdul Aziz, Zaridah Abdullah and Antashah Mohd Nor - Abdul Aziz, Ahlam; Abdullah, Zaridah; Mohd Nor, Antashah (UiTM Press, 2020)
This text book is written especially for Mass Communication students in degree programs who are taking Quantitative Analysis in Communication Research course. This book contains four chapters. Each chapter explained analysis with manual and SPSS example. Besides requires students to master in manual calculation, students also have to access SPSS statistical software. Examples with computer output provide opportunities for students to understand and interpret the data and result findings of a statistical analysis presented as computer output.